A formação inicial de professores e a cultura científica na educação básica: problematizando a prática docente na interface das disciplinas estágio supervisionado e história da física - Portela, Sebastiao Ivaldo Carneiro [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In this work, developed with a group of undergraduates, we have promoted some reflections and proposed some actinos concerning the scientific culture construction in secondary school, based on the initial formation influences of science understanding, the challenges faced in the school context and the process of preparation, construction and aplication of problem-solving-historical texts in schools. The experiment was performed in 2011, in a created space on the Supervised Practicum and the History of Physics disciplines interface; it involved a group of undergraduates from Unesp Engeneering College of Ilha Solteira - São Paulo, Brazil. This participated research has the purpose of analysing the process in which te undergraduates have lived, from the point of view of conditioning element manifestation of their practices, aiming, thereby, to expand the knowledge that justifiy the origin of the difficulties of the emancipation for transmitting Physics knowledge in schools environment. The collected data were drawn from the transcripts of discussions during the Supervised Practicum and the History of Physics classes, two semi-structured interviews and reports of the classes taught by the undergraduates in secondary schools. The analysis of the data contents points to the need of considering, in the professional prepartation of teachers, factors that influence their practices as cultural heritage of Physics teaching, the systemic forces, the specific knowledge of Physics teaching and the socio-organizational factors in the school context

Neste trabalho, junto a um grupo de licenciandos, promovendo reflexões e propomos ações voltadas à construção da cultura científica no Ensino Médio tomando como base as influências da formação inicial na compreensão da ciência, os desafios enfrentados no contexto escolar e o processo de preparação, construção e aplicação de textos, histórico-problematizadores nas escolas. A experiência foi realizada num espaço criado na interface das disciplinas Estágio Supervisionado e História da Física durante o ano de 2011 e envolveu um grupo de licenciandos em Física da Faculdade de Engenharia da Unesp da Ilha Solteira. O objetivo da pesquisa consistiu em analisar o processo vivenciado pelos licenciandos do ponto de vista das manifestações de elementos condicionantes de suas práticas, almejando, desse modo, ampliar os conhecimentos que justifiquem a origem das dificuldades de emancipação para a transmissão dos conhecimentos da Física nas escolas. Os dados coletados são oriundos das transcrições dos debates realizados nas aulas de Estágio Supervisionado e História da Física, de duas entrevistas semiestruturadas e dos relatos das aulas ministradas pelos licenciandos nas escolas de Ensino Médio. As análises dos conteúdos dos dados apontam para a necessidade de considerar, na preparação profissional dos professores, fatores que condicionam suas práticas como as heranças culturais do ensino de Física, as forças sistêmicas, os conhecimentos específicos do ensino de Física e os fatores sócio-organizacionais do contexto escolar
Keywords: Cultura; Ciencia; Fisica - História; Estagios supervisionados; Professores - Formação; Culture